2018
DOI: 10.1007/s11010-018-3444-3
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial Nod-like receptor NLRX1 modifies apoptosis through SARM1

Abstract: NLRX1, the mitochondrial NOD-like receptor (NLR), modulates apoptosis in response to both intrinsic and extrinsic cues. Insights into the mechanism of how NLRX1 influences apoptosis remain to be determined. Here, we demonstrate that NLRX1 associates with SARM1, a protein with a toll/interleukin-1 receptor (TIR)-containing domain also found in adaptor proteins downstream of toll-like receptors, such as MyD88. While a direct role of SARM1 in innate immunity is unclear, the protein plays essential roles in Waller… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…This attenuation of NLRX1 and subsequent elimination in mitochondrial ROS production was associated with improved cell survival, tight junction formation, and barrier function (43). Contrastingly, NLRX1 reportedly exerts protective effects against apoptosis in chondrocytes and tubular epithelial cells, and the modulation of apoptosis may be dependent on its interactions with yet another protein, SARM1 (37, 41, 75).…”
Section: Nlrx1 Regulates Immune System Function Through Mitochondria mentioning
confidence: 95%
“…This attenuation of NLRX1 and subsequent elimination in mitochondrial ROS production was associated with improved cell survival, tight junction formation, and barrier function (43). Contrastingly, NLRX1 reportedly exerts protective effects against apoptosis in chondrocytes and tubular epithelial cells, and the modulation of apoptosis may be dependent on its interactions with yet another protein, SARM1 (37, 41, 75).…”
Section: Nlrx1 Regulates Immune System Function Through Mitochondria mentioning
confidence: 95%
“…Lentiviral knockdown of HRI expression was performed as previously described (11) and HRI -/cell line generation and characterization was also previously described (11). Stimulation with TNF (10ng/ml, Cell Signaling technology) plus cycloheximide (10µg/ml) was performed similar to previously (49). MG132 and chloroquine were from Sigma.…”
Section: Cell Lines and Reagentsmentioning
confidence: 99%
“…Thus, NLRX1 may produce effects partly through inflammation and apoptosis pathways. NLRX1 has also been shown to regulate apoptosis via sterile alpha and Toll/interleukin-1 receptor motif containing protein 1 [ 12 ]. Moreover, a recent study showed that NLRX1 mediates mitophagy through its LC3-interacting region motif binding to LC3 in cells induced by bacterial pathogens [ 13 ].…”
Section: Introductionmentioning
confidence: 99%